Analisis Pengaruh Faktor-Faktor Literasi Keuangan Terhadap Keputusan Berinvestasi Pada Asuransi Jiwa di Kota Palembang - Resa Novita; Isni Andriana; Kemas M Husni Thamrin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The purpose of this research is to analyze the effect perceptions about financial literacy factors against the investment decisions on life insurance in Palembang. The population in this study is the owner of life insurance in Palembang, the sampling in this study is using the Purposive Sampling method with 50 respondents as samples. The type of research used is quantitative research with primary data sources obtained from distributing questionnaires to respondents. The data analysis technique in this research are descriptive and inferential statistical analysis using Structural Equation Modeling (SEM) with smartPLS (Partial Least Square) 3.0 software. The results showed that the perception of age and gender has no significant effect against the investment decisions on life insurance in Palembang, meanwhile the perception of education level and income have a significant effect against the investment decisions on life insurance in Palembang. Keywords: Age, Gender, Level of Education, Income, Investment Decisions